Metode Persuasif Kantor Camat Labuhanhaji Barat Dalam Mensosialisasikan Vaksinasi Kepada Masyarakat - Dian Novi Eriska; Anhar Fazri (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Study this background by enhancement total number vaccine to population districts LabuhanHaji west, hal this is feedback after existence socialization applied vaccines by subdistrict head LabuhanHaji west. Before existence activity socialization by party office subdistrict head many once pro and counter to vaccine. Study this aim for explain method what is applied office subdistrict head so that public interested for do vaccination. Method research used is method descriptive qualitative for explain research, get in- depth data from results interview with a number of informant. Study this use theory communication persuasive that is Theory Change attitude. Results study pointing that , the socialization carried out to public LabuhanHaji West get positive feedback , method applied persuasion by office subdistrict head on socialization vaccine succeed give understanding about importance vaccination for society and follow rule which set government center , use for eradicate the Covid-19 virus exist in Indonesia.